2022
DOI: 10.1097/prs.0000000000008956
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Research Practices in the Plastic Surgery Literature

Abstract: Background: Reproducible research—defined as the ability to replicate a study with its published materials and procedures—is integral to ensuring the validity of published studies and promoting scientific advancement. The primary aim of this study was to quantitatively evaluate the reproducibility and transparency of research in the plastic surgery literature. Methods: A cross-sectional study was performed. Articles published in 12 plastic surgery journals over a 5-year period were randomly selected. Reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…More literature searches identified another 44 eligible reports for inclusion, giving a total of 114 eligible meta-research studies examining a combined total of 2 254 031 primary articles for the review. 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More literature searches identified another 44 eligible reports for inclusion, giving a total of 114 eligible meta-research studies examining a combined total of 2 254 031 primary articles for the review. 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 ...…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary results in the supplementary information provides further information on the individual participant data retrieval process, as well as the outcomes of the data integrity checks. In total, 108 reports of 105 meta-research studies assessing a total of 2 121 580 primary articles were included in the quantitative analysis, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 ...…”
Section: Resultsmentioning
confidence: 99%
“…Study findings should be considered within the context of multiple limitations. Similar to recent reviews examining the presence of open practices in addiction medicine (Adewumi et al, 2021), cardiology (Anderson et al, 2021), obstetrics and gynecology (Rauh et al, 2022), oncology (Walters et al, 2019), orthopedics (Fladie et al, 2021), plastic surgery (Ascha et al, 2022), psychology (Hardwicke et al, 2022), and the social sciences (Hardwicke et al, 2020), we sampled only 250 studies (from a pool of 1,427 articles). Although we randomly selected these studies, results from a larger sample may have differed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is concerning that studies examining the reproducibility and transparency of research in plastic surgery, have found that the majority of publications fail to provide the information and raw materials to even make an attempt at replication of empirical studies possible. 27 Reframing quality and validity as part of the ethical imperative in research can improve transparency and collective progress as a field.…”
Section: Experimental Designmentioning
confidence: 99%